Planetary Wave Spectrum in the Stratosphere–Mesosphere during Sudden Stratospheric Warming 2018 - Yuke Wang; Gennadi Milinevsky; Oleksandr Evtushevsky; Andrew Klekociuk; Wei Han; Asen Grytsai; Oleksandr Antyufeyev; Yu Shi; Oksana Ivaniha; Valerii Shulga (Remote Sensing, 2021)
The planetary wave activity in the stratosphere–mesosphere during the Arctic major Sudden Stratospheric Warming (SSW) in February 2018 is discussed on the basis of microwave radiometer (MWR) measurements of carbon monoxide (CO) above Kharkiv, Ukraine (50.0° N, 36.3° E) and the Aura Microwave Limb Sounder (MLS) measurements of CO, temperature and geopotential heights. From the MLS data, eastward and westward migrations of wave 1/wave 2 spectral components were differentiated, to which less attention was paid in previous studies. Abrupt changes in zonal wave spectra occurred with the zonal wind reversal near 10 February 2018. Eastward wave 1 and wave 2 were observed before the SSW onset and disappeared during the SSW event, when westward wave 1 became dominant. Wavelet power spectra of mesospheric CO variations showed statistically significant periods of 20–30 days using both MWR and MLS data. Although westward wave 1 in the mesosphere dominated with the onset of the SSW 2018, it developed independently of stratospheric dynamics. Since the propagation of upward planetary waves was limited in the easterly zonal flow in the stratosphere during SSW, forced planetary waves in the mid-latitude mesosphere may exist due to the instability of the zonal flow.